Toward lifetime and g factor measurements of short-lived states in the vicinity of 208Pb. (20th April 2017) - Ralet, D; Georgiev, G; Stuchbery, A E; Clément, E; Lemasson, A; Michelagnoli, C; Rejmund, M; Atanasova, L; Balabanski, D L; Bocchi, G; Carroll, R; Dewald, A; et al.
Abstract: The multi-nucleon transfer reaction mechanism was used to produce and study nuclei in the vicinity of 208 Pb. This mass region is a test case for the nuclear shell model. The mass identification of the fragments was performed with the large acceptance magnetic spectrometer VAMOS++ coupled to the AGATA γ -tracking array. This experiment aimed to determine both lifetimes and gyromagnetic ratios of excited states with the Cologne plunger device. The analysis indicates promising results with the possibility to determine several new lifetimes in this region.